PEMBUATAN EKOSEMEN DARI SAMPAH ORGANIK - Rubin Nanda 2) dan Riant Anggraini 2), Nana Dyah Siswati, (Jurnal Teknik Kimia, 2009)
The Huge volume of urban garbage despite limited space of garbage dump and inappropriate handling have become complicated and never ended problem. Helped to these issue, the research on Forming Ecocement from organic garbage was carried out. Ecocement was made from the mixture of the ash of organic garbage and limestone. The ashing was started by putting up the dry leaves and branches and some anorganic garbage (i.e paper) in pirolisis reactor, heated at temperatures 100, 150, 200, 250, 300 (oC). The resulted ash was mixed with limestone at (60:40) ; (55:45) ; (50:50) ; (45:55) ; (40:60) (%) ratio and blended with water. Next, the mixture was heated in a temperature of 900 oC for 1 hour. The ash analysis from the pirolisis process indicated that the best ash to produce cement was one that was heated in the temperature of 300 oC in the composition of CaO = 200.591,8 ppm SiO2 = 160.020, 8 ppm Al2O3 = 56.800,9 ppm dan Fe2O3 = 5.510,6 ppm, while the best ratio of ash : lime stone is 55 % : 45 % in the composition of CaO=60,8 % , SiO2 = 16,3 % , Al2O3 = 4,8 %, Fe2O3 = 0,3%. The resulted cement stand the tensile strengt 72,6 kg/cm2, min, in 7 days stored (standard  grade of the tensile strengt 150 kg/cm2, min, in 7 days stored). Key words : Ecocement, Ash of Organik Garbage, Lime Stone.